Chinese literature in Belarusian criticism and literary studies of XX–ХХI centuries - Zhukavets, Veronika V. (Journal of the Belarusian State University. Philology, 2019)
The thesis is based on the system analysis of Chinese literature translations, literary articles were taken as a basis for working out periodization, which corresponds to the four cultural and historical stages of the development, occurring in the Belarusian cultural space: 1910 –1959; 1960 – beginning of 1985; 1985–1990; 1991 – till present. Considerable attention was paid to the individuality of Chinese writers’ creative thought, indisputable contribution of Belarusian literary critics (B. Rudman, G. Kashuba, A. Karljukevich, D. Factorovich, et al.) in study and popularization of Chinese literature of different periods of historical stages.
Keywords: Chinese literature; classical Chinese literature; modern Chinese literature; poetry; prose; cultural contacts; literary contacts; reception; translations; stages of development; history and criticism of literature